2008
DOI: 10.1375/bech.25.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of the FRIENDS Program in Reducing Anxiety Symptoms Among South African Children

Abstract: The prevalence of anxiety symptoms among South African children is reported to be significantly higher than in other parts of the world. The need for an effective anxiety prevention and early intervention program for use with South African children is urgently needed. The aim of the present study was therefore to determine whether the Australian FRIENDS program could effectively reduce the anxiety symptoms, as measured by the Spence Children's Anxiety scale (SCAS), among a sample of South African children from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
3
36
2
2
Order By: Relevance
“…Mostert & Loxton, 2008) where significant changes in anxiety symptoms are only visible at follow-up showing a sleeper effect. Previous research on FRIENDS for Life programme has generally shown a significant decrease in anxiety symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mostert & Loxton, 2008) where significant changes in anxiety symptoms are only visible at follow-up showing a sleeper effect. Previous research on FRIENDS for Life programme has generally shown a significant decrease in anxiety symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…; Lowry-Webster, , with gains maintained at three-year follow-up (Barrett, Farrell, Ollendick, & Dadds, 2006; Lowry-Webster, . Mostert and Loxton (2008) conducted a study with 12-year-old children from South Africa and found a significant reduction in anxiety for those receiving the programme. Stallard et al (2005) evaluated the programme implemented by school nurses in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The FRIENDS program has been tested in clinical settings, as well as in the school environment . Over the years, in line with the positive psychology movement, the author of the program shifted its focus from treating anxiety disorders in clinical settings, to a universal intervention delivered in school to promote general emotional health . Several studies have been conducted to evaluate the impact of the FRIENDS program and results have shown improvements in participant's self‐concept, social skills, and coping skills …”
mentioning
confidence: 99%
“…The FRIENDS program is an intervention that has been widely implemented over the last twenty years as a school-based universal prevention program to promote students' general social and emotional development (Barrett & Turner, 2001;Lowry-Webster et al, 2001;Lowry-Webster et al, 2003;Mostert & Loxton, 2008). Despite the effectiveness of interventions, such as the FRIENDS program, many schools experience significant geographical challenges to access the necessary training to deliver the programs or interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The FRIENDS program has been tested in clinical settings (Barrett, 1998;Barrett, Dadds, & Rapee, 1996;Barrett, Duffy, et al, 2001;Farrell, Barrett, & Claassens, 2005;Shortt et al, 2001) and in the school environment (Barrett, Lock, & Farrell, 2005;. Over the years, in line with the positive psychology movement, Dr. Barrett shifted its focus from treating anxiety disorders in clinical settings to a universal intervention that was delivered in schools to promote positive emotional health (Barrett & Turner, 2001;Lowry-Webster et al, 2001; Lowry-Webster, Mostert & Loxton, 2008). Several studies have been conducted in schools to evaluate the impact of the FRIENDS program and results have shown improvements in participant's self-concept (Stallard et al, 2005;Stallard et al, 2008;Stallard et al, 2007), social skills (Liddle & Macmillan, 2010), and coping skills (Stopa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%